THE CONSUMER BEHAVIOR OF PURCHASING DECISION REGARDING FAST MOVING CONSUMER GOODS IN RURAL AREA - Hidayat, Restya Nur; Hudrasyah, Herry (Journal of Business and Management, 2017)
Abstract. Background: this study aims to identify the factors that influence consumers’ purchase decision toward fast moving consumer goods on rural area. Methods: the objective of this study can be achieved by spreading the questionnaire with convenience sampling technique. The data is analyzed by using factor analysis and multi linear regression techniques.  Results: The findings from this research have found five factors that can influence to behavioral of society in the rural area in purchasing decision toward FMCG product. Conclusion: the findings of this study can be utilized in decision marketing strategy.  Keywords:  FMCG, purchase decision, analysis factor and multiple linear regression.